Simulation Study of Nanoparticle–Polymer Organic Suspension Stability. Issue 5 (15th March 2019) - Lu, Kathy; Gervasio, Michelle
Abstract: This study uses a Monte Carlo simulation method to evaluate the agglomeration behaviors of different ZnO nanoparticle and polymethacrylate hybrid suspensions in an organic solvent. Interaction energies are primarily from the steric layer on the particle surfaces. The effects of nanoparticle size, steric layer thickness, particle content, and total solids loading are evaluated based on the average agglomerate size and agglomeration rate. Smaller particle, thicker steric layer, lower particle content, and higher solids loading are desirable factors to stabilize a suspension. Agglomerate size and agglomeration rate increase continuously with increasing particle content in the hybrids from 1 to 50 vol%. A drastic transition from an unstable suspension to a stable suspension occurs when the total solids loading of the suspension increases to greater than 10 vol%. This work provides important guidance for co‐dispersing nanoparticles and dissolved polymer chains in organic solvents. Abstract : This work provides important guidance for co‐dispersing nanoparticles and dissolved polymer chains. It presents a constant number Monte Carlo simulation method for nanoparticles and polymer organic co‐suspensions. Interaction energies are primarily from the steric layer on particle surfaces. A drastic transition from an unstable suspension to a stable suspension occurs at a critical total solids loading.